MANAJEMEN BUDAYA ORGANISASI MADRASAH ADIWIYATA: MANAJEMEN BUDAYA ORGANISASI MADRASAH ADIWIYATA - Sudarto Murtaufiq, Victor Imaduddin Ahmad (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2020)
ABSTRACT This study is aimed at answering the following three research questions: firstly how is the implementation of organizational culture management in MAN 1 Lamongan; secondly, how is the organizational culture model in MAN 1 Lamongan and thirdly how are its implications. The implementation of organizational culture management in MAN 1 Lamongan includes four aspects, namely environmentally friendly policies, integrated environment-based curriculum implementation, participatory-based environmental activities and the management of environmentally friendly supporting infrastructure. The organizational culture model includes four components; firstly, the determination of the values ??and vision of the madrasa, secondly, internalizing the vision of all stakeholders; thirdly the conceptual embodiment; fourthly, the behavior embodiment and fifthly, the embodiment of symbolization. In terms of the implications of organizational culture management in MAN 1 Lamongan, there is an increase in quality in three aspects, firstly, from the environmental aspect, it could be concluded that MAN 1 Lamongan has increasingly become more qualified; secondly, from the aspect of students, there is an increase in environmental awareness that includes three aspects, namely cognitive, psychomotor and affective. And thirdly from the aspect of the level of satisfaction of education services, there is an increase in the IKP points, which in 2018 amounted to 73,634 and in 2019 amounted to 74,514. Keyword: Management, Organizational Culture, Madrasah